Study of Transformer Core Vibration and Noise Generation Mechanism Induced by Magnetostriction of Grain-Oriented Silicon Steel Sheet - He Qiang; Nie Jingkai; Zhang Songyang; Xiao Weimin; Ji Shengchang; Chen Xin (Shock and Vibration)
The problem of vibration and noise in the iron core of power transformers remains quite topical. Insofar as the state-of-the-art iron core and binding production adopt the lamination method and weft-free adhesive tape, respectively, the transformer core vibration is mainly attributed to the silicon steel sheet (SSS) magnetostriction. In this paper, based on the magnetostriction of grain-oriented SSS, an in-depth analysis of the vibration generation mechanism in the transformer core was performed. The SSS microstructure was observed, its magnetostrictive properties at different magnetic flux densities were tested, and a core-simulating four-corner iron core model was constructed to analyze the vibration characteristics. Modal, vibration, and noise tests were performed on an actual 110 kV transformer core under no-load conditions. The results show that the core vibration is related to SSS’s deformation mechanism. The vibration magnitude in different core parts varies due to the magnetostriction anisotropy. The vibration in vertical to the core plane is the largest, and its magnitude in the core center is lower than those at the seams in the same plane. The core vibration and noise exhibit a significant correlation, while modal characteristics strongly influence the core vibration and noise intensity.